1999
DOI: 10.1021/jp984737a
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Rod-Shaped Gold Particles by Electric Fields

Abstract: The electro-optical response of colloidal dispersions of rod-shaped gold particles is studied for various aspect ratios (2.6 < L/d < 49; d ) 15 nm) by monitoring the absorbance spectra in the visible wavelength regime. The absorbance spectra strongly depend on the degree of orientational order of the rods and the direction of the polarization of the incident light with respect to the applied electric field. From the change in absorbance of the transverse resonance the electro-optical effect is deduced: at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
119
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 26 publications
8
119
1
Order By: Relevance
“…The collective oscillation of the conduction band electrons in noble metal nanoparticles gives rise to very large scattering and absorption cross-sections (23). In addition to the high photostability (22), lack of photoblinking (24), and excellent biocompatibility (25), the polarization of the absorbed scattered light can be tuned readily through the shape of the nanoparticles allowing for orientational imaging (26). One of the best studied metallic nanoparticles with an anisotropic shape are Au NRs that have longitudinal and transverse SP modes polarized parallel to the long and short axes of the NRs, respectively (27).…”
mentioning
confidence: 99%
“…The collective oscillation of the conduction band electrons in noble metal nanoparticles gives rise to very large scattering and absorption cross-sections (23). In addition to the high photostability (22), lack of photoblinking (24), and excellent biocompatibility (25), the polarization of the absorbed scattered light can be tuned readily through the shape of the nanoparticles allowing for orientational imaging (26). One of the best studied metallic nanoparticles with an anisotropic shape are Au NRs that have longitudinal and transverse SP modes polarized parallel to the long and short axes of the NRs, respectively (27).…”
mentioning
confidence: 99%
“…[11] Other researchers have shown that orientation can be induced in both conductive and dielectric rod-shaped particles dispersed in a suitable solvent. [22,23] We chose to investigate electric-field-induced orientation of molecular-sieve crystals dispersed in solvents to develop a technique to deposit the crystals as a film with controlled crystal orientation. Fibrous aluminum phosphate number five (AlPO 4 -5) molecular-sieve crystals were synthesized following previously described procedures.…”
Section: Methodsmentioning
confidence: 99%
“…26 In 1997, van der Zande et al achieved electrochemical deposition of gold in mesoporous silica pores. 27,28 In this study, a hard template, a stiff porous layer on an electrode, regulated the shapes of nanoparticles and enabled the electrochemical deposition of uniform rod-shaped nanoparticles. The nanorods could be dispersed in an aqueous solution, showing two remarkable SP bands originating from the anisotropic shapes.…”
Section: Introductionmentioning
confidence: 99%